How Do Firms Form Expectations of Aggregate Growth? New Evidence from a Large-Scale Business Survey - Dovern, Jonas; Müller, Lena Sophia; Wohlrabe, Klaus (2020)
Expectations are highly relevant for macroeconomic dynamics. Yet, the empirical evidence about properties of corporate macroeconomic expectations is scarce. Using new survey data on quantitative growth expectations of firms in Germany, we show that expectations are highly dispersed. The degree of dispersion depends on firm size and on how important the general economy is for the business of firms, supporting theories of rational inattention. Firms seem to extrapolate from local economic conditions and business experiences to aggregate growth expectations. Differences in growth expectations are associated with differences in firms’ investment and labor deman
Keywords: GDP expectations; expectation heterogeneity; firm; ifo business tendency survey